Accompany and train. Mentoring as a tool to reduce school dropouts - Vázquez Parra, José Carlos (2018)
University studies not only mean a process or stage of professional training for young people, but also a moment in their lives that presents them with different challenges that require them to develop disciplinary, social and personal competences. Unfortunately, if the young person does not manage to overcome this test, the problems that this stage brings will overcome him, binding himself in situations that hewill simply be unable to face. Therefore, universities must find pedagogical tools that not only see the academic development of their students, but also the adoption of coping skills that allow them to improve as people. This article seeks to present an approach to mentoringas a possible accompaniment tool that can indirectly reduce the dropout rate by improving the learning experience of university students.